Permanência e abandono escolar na educação profissional: um estudo sobre Instituições Federais de Joinville e Jaraguá do Sul - Coelho, Alexsandra Joelma Dal Pizzol (2014)
Presenting the results of research that aimed to analyze, from the perspective of students and ex-students of concomitant and subsequent technical courses in industrial area, motivations and reasons that justify or explain the permanency or abandonment to their curses. Based on the conception of the work as a central category and educational principle, relied on references to Marx, Gramsci, Frigotto, Gadotti, Kuenzer and Paulo Freire, as well as Dubet, Rui Canário, Fornari, Baeta, Dore, among other authors from different sources and theoretical conceptions seeking dialogue between them and deepen the theoretical and ideological conflicts that permeate discussions on the school permanency or dropout. From a qualitative exploratory approach, the research involved both students persevering and who have dropped the concomitant courses in public institutions in Joinville e Jaraguá do Sul, in Santa Catarina, in the period between the 2nd semester of 2011 until the end of 2013, by the application of questionnaires and interviews. 270 persevering students responded to the questionnaire; of the students who had dropped out, 13 responded to the questionnaire and 10 were interviewed. The analysis of information was guided into categories relating to internal and external to school factors, didactic and pedagogical factors and public policies supporting school permanency, seeking the dialectical relationship between them. It is evidenced in this work the dearth of research on dropout and school permanency, particularly in professional education. The results have signaled there is a complex and contradictory relationship between the drivers of abandonment and permanency, sometimes appearing as motivators to stay and other times as drivers of abandonment, standing out among these those the relation established between teachers and educators and the relationship between work, study and family, which are presented as motivation for permanency and/or dropout. It was pointed out also that the current policies supporting permanency in the surveyed institutions are not recognized by students and identified as critical for school permanency, being characterized more like politics and income transfer than incentive to study. It has evidenced the need for further studies and research on the dropout and permanency in professional education.